Development of Learning Materials on Fiqh of Alcohol and Khamr in Islamic and Science Perspective - Rafika Dwi Rahmah MZ; Suyadi; Zahrul Mufrodi (International Journal of Science and Society, 2020)
The law of alcohol and khamr are often equated in Islamic fiqh, even though they are both different in terms of substance and character. The purpose of this study was to test the scientific experimental approach between alcohol and khamr in Islamic religious education learning at the Junior High School 6 PGRI Denpasar, Bali. This experiment will have implications for changing students' perspectives on alcohol which has two fiqh laws, while khamr is certainly haram even though the substance contained in khamr is not alcohol. This study used an experiment with a comparison between the science experimental method class and the control class using the lecture method. The results of the validation of media experts, materials and teachers were 93% with perfect criteria. The pretest in the experimental class has a percentage of 72.5% and the experimental class is 68.5% in the control class. Postest in the experimental class percentage of 87.25% of great criteria, while in the control class the value was not much different from the presentation in the experimental class 73. The difference between postest in the experimental class and control class is 14.25%. Based on the results of the validation and pretest-posttest comparisons between classes, the experimental method is well applied to Islamic Religious Education learning.